English-Arabic Language Contact Phenomena In Social Media As Communicative Learning - Ahmad Saifulloh; Ardiati Lutfiatul Naziroh; Nur Kholis (Ijaz Arabi Journal of Arabic Learning, 2023)
The issue of contact meaning in communicative learning has received considerable critical attention. Translation and contact meaning are two terms that have enjoyed interpretation in modern language studies. Contact meaning is required to understand translation. Language contact is the social and linguistic phenomenon by which speakers of different languages. This paper describes Arabic and English contact phenomena. This article aims to identify relationships between English-Arabic contact meaning elements and increase forms of communicative learning in social media through social media. This study has limitations; the data were collected from one social media platform, Instragram reel account english_with_ms_zainab. This study shows that the English-Arabic contact phenome has some categories: interlanguage, the tip of the tongue, hypercorrection, and cross-cultural understanding. Using social media could improve students’ communication ability by learning through an Instagram reel as a social media.